Caregiver, community health worker, and dentist feedback on a behavioral intervention for caregivers of children with severe early childhood caries - Paige Patano; Teresa G. Borowski; Melanie Izquierdo; Calvin Wong; David Avenetti; Helen H. Lee; Helen H. Lee; Joanna Buscemi (Frontiers Media S.A., 2024)
IntroductionSevere early childhood caries (S-ECC) is a common disease within marginalized pediatric populations. S-ECC is often treated under general anesthesia to facilitate extensive treatment in young children, but treatment does not address etiology of an infectious disease that is rooted in health behaviors. Without behavior changes related to toothbrushing and sugar consumption, many children experience recurrent disease and some require subsequent surgeries. To improve post-surgery oral health, we developed PROTECT (Preventing Recurrent Operations Targeting Early Childhood Caries Treatment), a community health worker (CHW)-delivered behavioral intervention for caregivers that focuses on children's oral health behaviors. The purpose of this study was to use qualitative research methods to receive feedback on the planned protocol for a pilot study of PROTECT, a six-month intervention initiated at the time of a child's surgery to treat severe early childhood caries.MethodsStudy participants included caregivers of children presenting for surgery [n = 12], CHWs [n = 8] and dentists [n = 8] in a series of audio-video recorded semi-structured interviews. Five coders used Braun and Clarke's six-phase framework for data analysis.ResultsParticipant feedback on the pilot study protocol yielded the following themes: (1) right time, population, and type of support; (2) flexible intervention delivery and content; (3) inclusion of other social determinants of health; and (4) cultural considerations. Implementing a behavioral intervention for caregivers in the immediate time during a child's surgery for treating dental caries was widely deemed important and timely in order to affect post-surgical behavioral and clinical outcomes. Flexibility in content, timing, and communication were all named as facilitators to participant engagement and study retention. Caregivers and CHWs emphasized the relevance of addressing other social determinants of health. CHWs emphasized the importance of training in becoming aware of culture and practicing with understanding and humility, given the influence on health beliefs, behaviors, and family dynamics. Cultural considerations in intervention delivery were deemed an important factor for participant retention and engagement.DiscussionParticipant feedback led to critical modifications of the pilot study protocol, specifically in intervention content and CHW-led delivery.